Efektifitas Terapi Komplementer dalam Meningkatkan Kekuatan Otot Pasien Stroke : A Literature Review - Ianah Al Azizah; Ikhlas Muhammad Jenie (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
AbstractÂ Background:Irregular life style such as irregular eating pattern, lack of exercise, overwork and excessive consumption of fast food has become common habit and is potential for developing a risk of stroke. Post stroke patients are generally experiencing muscle weakness on their parts of limb, postural disorder and muscle atrophy. Complementary therapy can be an alternative to increase muscle strength of patient with stroke.Objective:Identifying the effectiveness of complementary therapy to increase muscle strength of patient with stroke.Method:This literature review used database from PubMed, Proquest, and Google Scholar.Â During the initial stage, the keyword of: â€œ((Complementary AND Muscle strength AND Stroke Complementary Therapy))â€ resulted in the total of 12 international articles ranging from year 2016 to 2018 which all are in line with the criteria of inclusion and exclusion.Result:The research articles used were those of conducted in various countries such as: Turkey, South Korea, China, Australia, Dutch, Germany, Brazil, New Zealand, America and Indonesia. The number of articles being compiled was in total of 12 articles, the majority of the research respondents were patients with stroke. The literature review consisted of the effectiveness of several complementary therapies to increase muscle strength of patient with stroke. The review gave description of how complementary therapy intervene with the increasing of muscle strength of patient with stroke in several countries. The type of research included within the review found by the author was that of quantitative research in total of 12 articles.Conclusion:It was concluded that those various articles were related with several complementary therapies to increase muscle strength on patient with stroke. There are several complementary therapies that can be used to increase muscle strength on patient with stroke; those are: mirror therapy, mental practice (MP) and mental practice mirror therapy (MPMT), aquatic treadmill, robotic therapy, and acupuncture.